"I am Out of My Comfort Zone": Self-study of the Struggle of Adapting to the Professional Identity of a Teacher Educator. Issue 3 (1st September 2016) - Allen, Jared; Park Rogers, Meredith; Borowski, Rebecca
Abstract: It is often assumed that graduate students will develop as teacher educators simply by participating in a doctoral program. However, research has shown that doctoral students find the shift from teaching K-12 to preparing teachers to be a difficult transition. Within the context of a doctoral program community of practice established specifically for the purpose of examining this transition through self-study research, we sought to understand the shift in identity of a novice teacher educator working as an early field experience instructor with elementary science and mathematics preservice teachers. Our findings indicate that the process of self-study research, when supported within a community of practice, offered Jared the opportunity to recognize different aspects of his shifting professional identity, the dominance of particular aspects of his identity in certain situations, and the impact this was having on his students' development as teachers. Developing this awareness of his adapting professional teaching identity from a classroom teacher to a teacher educator should help as he continues to develop his knowledge and skills working with teachers in different contexts and at different grade levels. Implications for how teacher education programs could better support the professional identity development of novice teacher educators through the use of a self-study focused community of practice are discussed.